Prototype of Automatic Waste Object Picking Robotic Arm in the Working Room - Ari Yudha Putra Pratama; Nina Paramytha IS (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
A robotic arm or robotic arm is a mechanical robot that resembles a human arm programmed with functions similar to a human arm. Robotic arms are widely used in today's modern industrial world. But not many use robotic arms for purposes outside the industrial world. Robots can also be useful for the environment around us, for example, for collecting trash in the workspace. From these problems, the researcher aims to create a prototype tool for a robotic arm that automatically collects garbage objects in the workspace which has several components such as a no-touch sensor to read other sensor data, an ultrasonic sensor to read garbage objects in front of the robotic arm, a proximity sensor to function as a navigation arm. A moving robot, a load cell sensor to determine the weight of a trash object, and a 16x2 LCD to determine the battery percentage, and if the object exceeds a predetermined weight, which is less than 200 grams and functions for a temporary full trash box, the indicator is in the form of a sound buzzer that will sound. This prototype tool can help employees clean their rooms and collect trash at work to make the workspace cleaner and more organized.